1984
DOI: 10.1002/jmv.1890130405
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with primary cytomegalovirus infection during pregnancy

Abstract: We compared a group of 40 susceptible pregnant women who acquired CMV during gestation with a group of 86 women of similar race and socioeconomic background who remained seronegative to define factors associated with the risk of CMV infection during pregnancy. A logistic regression model using a stepwise procedure showed that a positive statistically significant correlation occurred with the age of the mother, the father's high-intensity contact with young children, and children living at home. A negative corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…Contacts are of central importance in the transmission of most infections; and clearly some occupations involve contacts with more individuals than others. An association between 'highcontact' parental occupations and an infectious disease in their children has already been noted in studies of poliomyelitis (McFarlan et al, 1946;Cowan, 1950;Benjamin and Logan, 1953;Logan, 1953;Backett, 1957) and cytomegalovirus infection (Stagno et al, 1984;Adler, 1988;Pass et al, 1986Pass et al, , 1987Murph et al, 1991). A question that reasonably follows is whether, in population-mixing situations associated with an excess of childhood leukaemia, children whose fathers have contact with many different people at work have a higher incidence of this disease than the children of men with lower levels of work contacts.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Contacts are of central importance in the transmission of most infections; and clearly some occupations involve contacts with more individuals than others. An association between 'highcontact' parental occupations and an infectious disease in their children has already been noted in studies of poliomyelitis (McFarlan et al, 1946;Cowan, 1950;Benjamin and Logan, 1953;Logan, 1953;Backett, 1957) and cytomegalovirus infection (Stagno et al, 1984;Adler, 1988;Pass et al, 1986Pass et al, , 1987Murph et al, 1991). A question that reasonably follows is whether, in population-mixing situations associated with an excess of childhood leukaemia, children whose fathers have contact with many different people at work have a higher incidence of this disease than the children of men with lower levels of work contacts.…”
mentioning
confidence: 79%
“…The high prevalence of cytomegalovirus infection among young children in nurseries is now well established as constituting a risk to their care-workers, who may then infect their own children (Stagno et al, 1982(Stagno et al, , 1984Preece et al, 1984;Pass et al, 1986Pass et al, , 1987Alder, 1988;Yow, 1988;Murph et al, 1991). An increased risk of cytomegalovirus infection has also been found among the children of fathers with occupations, or other activities, that involve much contact with children (Stagno et al, 1984).…”
Section: Parental Occupation and Childhood Infectionmentioning
confidence: 99%
“…However, an increased risk of cytomegalovirus infection is well established among the children of nursery workers and of certain other child-linked groups (Stagno et al, 1982(Stagno et al, , 1984Adler, 1988;Yow et al, 1988;Murph et al, 1991). Epidemics of paralytic poliomyelitis have occasioned similar observations about the children of teachers and of men in other high contact occupations (McFarlan et al, 1946;Cowan, 1950;Logan, 1953).…”
Section: Discussionmentioning
confidence: 99%
“…The notion of an increased risk of infection among the children of people in certain occupations is less familiar. In cytomegalovirus infection, however, an increased risk is well established among the children of both nursery workers and fathers with occupations, or leisure activities, involving much contact with children (Stagno et al, 1982(Stagno et al, , 1984Adler, 1988;Yow et al, 1988;Murph et al, 1991). Certain epidemics of paralytic poliomyelitis also occasioned similar observations (Cowan, 1950;Logan, 1953;McFarlan et al, 1946), while a study of poliovirus antibody levels in relation to social factors found that a higher than average level for an individual's social class was often associated with a high-contact occupation (Backett, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…Teaching and other occupations carried out in educational establishments (taken as those with the words 'child', 'school', 'college' or 'nursery' in the title) were therefore allocated to a very-high-exposure category, as in a study of cytomegalovirus infection (Stagno et al, 1984). Also included here were occupations taking people outside their local community (transport etc.…”
Section: Very-high-contact Levelmentioning
confidence: 99%